Keefektifan Penggunaan Media Peta Konsep Pohon Jaringan Dalam Pembelajaran Menulis Cerpen Pada Siswa Kelas X SMA Negeri 1 Labakkang Kabupaten Pangkep - Akram Nur; Fahirah Akib (Journal of Practice Learning and Educational Development, 2025)
This research aimed to describe the effectiveness of the utilization of concept map media of network tree on writing short story learning of X grade students at SMAN 1 Labakkang of Pangkep Regency with as many as 170 students spread in 6 classes. Design used in the study was true experimental design bentuk posttest-only control design. The results of the study revealed that (1) the average of pretest of the experiment class was in low category by 6,22, whereas the average of post-test was in extremely high category by 8,67. The improvement of short story writing skills of the experiment class was 2,45 which indicated that there was significant improvement on short story writing skills of students; (2) the average score of pretest of the control class was in low category by 6,03, whereas, the average of the post-test was in fair category by 6,72. This indicated that there was improvement on short story writing skills of students but not significant; (3) the concept map media of network tree was effective to be used in short story writing skills of X grade students at SMAN 1 Labakkang in Pangkep district indicated by the tcount 8,488 > ttable 2,00 or tcount > ttable meaning that H1 was accepted.